2023
DOI: 10.7554/elife.81779
|View full text |Cite
|
Sign up to set email alerts
|

MCT1-dependent energetic failure and neuroinflammation underlie optic nerve degeneration in Wolfram syndrome mice

Abstract: Wolfram syndrome 1 (WS1) is a rare genetic disorder caused by mutations in the WFS1 gene leading to a wide spectrum of clinical dysfunctions, among which blindness, diabetes and neurological deficits are the most prominent. WFS1 encodes for the endoplasmic reticulum (ER) resident transmembrane protein wolframin with multiple functions in ER processes. However, the WFS1-dependent etiopathology in retinal cells is unknown. Herein, we showed that Wfs1 mutant mice developed early retinal electrophysiological impai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
3
6
0
Order By: Relevance
“…This, combined with the unfolded protein response observed in the retina and optic nerve, suggests that we are looking at the earliest stages of disease, during which neuronal dysfunction is accumulating, but has not yet reached the tipping point towards cellular loss. Indeed, our findings confirm previous results in the same mouse model, in which neurodegeneration of the retinal ganglion cells was not seen at 8 months but manifested at 12 months [59], and mirror a study in WS patients, in which it was found that retinal ganglion cell axonal degeneration precedes cell body atrophy by about a decade [5]. Given the detrimental phenotype of this transgenic model, and applying humane end points, we limited our study to a maximum age of 7.5 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This, combined with the unfolded protein response observed in the retina and optic nerve, suggests that we are looking at the earliest stages of disease, during which neuronal dysfunction is accumulating, but has not yet reached the tipping point towards cellular loss. Indeed, our findings confirm previous results in the same mouse model, in which neurodegeneration of the retinal ganglion cells was not seen at 8 months but manifested at 12 months [59], and mirror a study in WS patients, in which it was found that retinal ganglion cell axonal degeneration precedes cell body atrophy by about a decade [5]. Given the detrimental phenotype of this transgenic model, and applying humane end points, we limited our study to a maximum age of 7.5 months.…”
Section: Discussionsupporting
confidence: 92%
“…At this age, we observed a mild and complex disease phenotype in the optic nerve, with alterations in axonal conduction strength combined with subtle thinning of the myelin sheath and a reduction of the OPC pool. Again, these findings are in line with a previous study in this Wfs1 Dexon8 mouse model [59], as well as in Wfs1 Dexon2 mouse and Wfs1 Dexon5 rat models [7,53]. Novel findings in our study originate from ex vivo measurements of optic nerve CAPs, which allowed us to investigate a potential defect in the optic nerve while excluding the retinal ganglion cell bodies and synapses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mouse model for the WFS1 syndrome that lacked two-thirds of the WFS1 gene reproduced all clinical features of this complex disease, like diabetes and mental disorders [ 47 ]. Within many years, several studies based on this mouse model have been published to describe the variable phenotypic effects of the mutation [ 57 , 58 ]. Very briefly, we have identified the growth retardation and development of combined endocrine disorders, combined with diabetes, in WFS1 mutant mice [ 39 , 48 , 50 , 59 ].…”
Section: Wolfram Syndrome Animal Modelmentioning
confidence: 99%
“…Therefore, we hypothesized that a lack of su cient PDH activity in WFS1 and CISD2 de cient neurons might diminish mitochondrial ATP production and, consequently, push the neuronal metabolism toward glycolysis. Indeed, several lines of indirect evidence suggest that a similar mechanism might be involved in WS 10,31,32 . First, the mitochondrial membrane potential, which re ects the e ciency of the NADHpowered mitochondrial respiratory chain, was slightly lower in WFS1-and CISD2-de cient neurons (Fig.…”
Section: Low Mitochondrial Ca 2+ Contributes To Poor Atp Productionmentioning
confidence: 99%